Implementation of CRISP-DM for Social Network Analysis (SNA) of Tourism and Travel Vlog Content Reviews - Singgalen, Yerik Afrianto (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
Technological developments have facilitated the process of creating and publishing digital content on various platforms while influencing application user behavior in terms of consumption. In the context of tourism and travel vlog content, the publication of travel content influences perceptions and triggers the intention of visiting the destination in which the video is taken. In addition, content reviews can be seen in the comment column, which shows the response from content creators to tourists related to the topics discussed in the video content. This study aims to analyze content reviewers' social network patterns and sentiments using the Cross-Industry Standard Process for Data Mining (CRISP-DM) approach. Meanwhile, the model used in this study is Social Network Analysis (SNA) and Sentiment Classification based on analyzing network patterns of "whom, mention whom," and "who replies who," based on diameter, density, reciprocity, centralization, and modularity. The stages in the CRISP-DM method consist of business understanding, data understanding, modeling, evaluation, and deployment. The results of this study show that at the business understanding stage, tourism and travel vlog content reviews with Waseda Boys Indonesia Trip video comment datasets and Waseda Boys Trip to Manado and Likupang video and Waseda Boys Trip to Labuan Bajo video. Scraping content review data from the YouTube platform is carried out at the data understanding stage based on author, description, Global Unique Identification (GUID), like_count, link, pub_date, and author channel URL. In the modeling stage, the interaction pattern between authors in the form of networks is visualized and analyzed based on clusters. At the evaluation stage, an evaluation is carried out based on sentiment related to content related to tourism activities. At the deployment stage, recommendations for digital tourism marketing strategies based on tourism and travel vlogs can be known. Thus, tourism and travel vlog content play an important role in triggering tourism intentions so that it is effectively used in destination marketing strategies in the digital era.